Comparison of Mathematics and Humanitarian Sciences Students' Metacognitive Strategies - Gholam Hossein Javanmard Javanmard (Universitas Ahmad Dahlan, 2014)
AbstractThe purpose of this study was to compare the differences of using meta-cognitive strategies in high school students who study in the fields of mathematics and humanities. For do this, 140 high school students were selected randomly. The Swanson’s Meta-cognition Strategies Test was administrated for sample groups. The acquired means for two regroups were compared with t-test for two independent groups’ method. Results indicated that two groups were meaningfully differed from each other (sig=0.01) in using meta-cognitive strategies, and mean of students in mathematics field were high. Also there was a meaningful difference in task component between two groups (sig=0.002), and the mean of students in mathematics field was higher than from students in humanities field in this component. The high school students in mathematics field use more metacognitive strategies, especially task component, than the students in humanities field.Keywords: metacognitive strategies, students, mathematics field, humanities field